Using Inside-Outside Circle Method to Enhance Students’ Speaking Skill - Suryadi Suryadi; Fajar Erlangga (Journal of English Language Studies, 2020)
This study aims to determine the application of the inside-outside method to enhance students' speaking skills. The design of the research is a true experimental study with Pre-test-Posttest Group Design. Learning outcome data are obtained through pretest and posttest activities. The samples are 80 students randomly taken by adjusting to the condition and aim of the research. There is a significant difference from the results of the experimental class posttest and control class this is evidenced by the Fo value. Fo value is 5.225 and Sig is 0.025 <0.05. It means that there is a difference in an interaction effect of using inside-outside circle method to enhance students’ speaking skill.